A hole in the wall of fortress Europe: The trans‐European posting of third‐country labour migrants. (17th May 2021) - Lens, Dries; Mussche, Ninke; Marx, Ive
Abstract: This article documents and discusses the importance of the intra‐EU posting of third‐country national (TCN) labour migrants. TCN labour migrants have traditionally been fixed to one Member State where they reside and work based on a work and residence permit. Case‐law of the European Court of Justice allowed TCNs to be posted across the EU based on the free movement of services. We reveal that an increasing number of TCNs from a large variety of citizenships are indeed mobile across the EU as posted workers. We additionally show that most of these workers are low‐ and medium‐skilled and would – in a traditional labour migration setting – have difficulty obtaining a work and residence permit from Member States that privilege highly skilled labour migration. We also demonstrate that the posting of TCNs has the potential to grow into a mobility channel on equal footing with "traditional" TCN labour migration.